Carrying capacity approach for agriculture land management in land subsidence area of West Java province - Giwangkoro, Aqila Janitra Sigfreda; Nabila, Tiffana Fakhriyati; Zayyin Asrofi, Muhammad; Jati Dewantara, Erlangga; Fitria Putri, Ratih (EDP Sciences, 2023)
West Java is one of the provinces in Indonesia which has high agricultural productivity. That way, it is necessary to carry out an analysis of the carrying capacity of agricultural land in West Java Province in 2022. The method used to calculate carrying capacity of agricultural land is the combination of Odum, Christeiler, Howard, and Isard theories which is suitable for local conditions and can assess the factors that affect the level of carrying capacity of land in an area. West Java Province has a carrying capacity of agricultural land of 0.74. The value of population pressure in West Java Province with a dominance of less than 1 indicates that districts/cities in West Java Province are dominated by the carrying capacity of high agricultural land. The high rate of population growth and not accompanied by an area of land capable of supporting the needs of the population can be a threat to the availability of sustainable agricultural land. © 2023 EDP Sciences. All rights reserved.